Investment Opportunity, Institutional Ownership, and Excess Cash Holdings with Financial Constraint as Moderation - Indriana Rezkia Putri; I Wayan Nuka Lantara (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study examines the effect of investment opportunity and institutional ownership on excess cash holdings with financial constraint as the moderating variable. Holding more cash is often rated as a negative signal for shareholders, because of the probability to use the cash inappropriately and increase the agency cost. Another side, excess cash can give a good impact on the company when is more expensive to access the external financing, or the situation make the firm had financial constraints. This study uses excess cash holdings as a dependent variable with few references and a high chance for further research. Generalized least square (GLS) is employed to analyze the hypothesis with observations during 2015-2020 in listed companies on Indonesia Stock Exchange (IDX). The result of this research shows that investment opportunity has a positive influence on excess cash holdings. If there is a financial constraint, it will decrease the effect of Investment opportunity to the level of excess cash holdings. This study was unable to capture the impact of institutional ownership on excess cash holdings in constraint nor unconstraint firms. The study was robust enough when the proxy of excess cash changed and when using the lag variable to confirm the primary result.